Pengembangan Modul Keuangan Pada Aplikasi Point of Sales Berbasis Android - Dwi Hosanna Bangkalang; Nina Setiyawati (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
In this community service activity, a financial module was added to the point of sales application that had been previously implemented at MSME Marikh Salatiga. This is because the issue of financial flows has not been accommodated which requires several different accounts. In addition, it is necessary to arrange an online food commission. The development of this module is expected to accommodate financial flows in Marikh Salatiga so as to avoid mismatches in the nominal balance of the entire account and can be monitored in real time. From community service activity with Marikh Salatiga partners, it can be concluded that the financial module implemented in the point of sales application helps Marikh Salatiga make it easier to monitor balance positions in various payment method accounts and can provide more valid financial flow information